Range of motion in selected joints in relation to sports performance and technique effectiveness in weightlifting - Kruszewski, M.; Kruszewski, A.; Tabecki, R.; Mierzejewski, B.; Pagowski, L. (Polish Journal of Sport and Tourism, 2022)
The aim of the study was to verify or falsify the role of flexibility as the ability that distinguishes weightlifting champions from their rivals in lower sports classes. The aim of the study was also to assess the relationship between the results in snatch and clean and jerk, technique effectiveness, mobility in the shoulder joint, dorsal extension of the foot and forward bend-ing of the spine. Material and methods. The study included 24 men training weightlifting - members of the Polish national team (n = 10) and members of one of Warsaw sports clubs (n = 14). Measurements were performed of active ranges of movement of the shoulder, flexion and extension in the shoulder joint, forward bending of the spine and dorsal extension of the foot in the ankle joint. The technique efficiency coefficients were calculated and the sports results were converted into Sincair points. Results. Significant differences (p = 0.05) were noted in dorsiflexion of the foot in the ankle joint and forward bending of the spine in the tested groups. National team members were characterised by higher mobility than sports club members. There were no significant differences in flexion and extension movements at the shoulder joint between the groups. Conclusions. Significant correlations were found between the range of forward bending of the spine (p = 0.001) and the range of dorsiflexion movements of the right (p = 0.001) and left (p = 0.01) foot, and sports performance in the snatch and clean and jerk, as well as in technique effectiveness. Achieving high sports performance in weightlifting may be limited by a low joint range of motion.